A spatial approach to rainfall in Sertão do Pajeú – Pernambuco (Research, Society and Development, 2021)
Changes in precipitation have implications for the hydrological cycle and water resources. Climate change is expected to alter average temperature and precipitation values, increasing the variability of these events, which could cause more intense and frequent floods and droughts. The objective of this study was to characterize the rainfall in the microregion of Pajeú, in Pernambuco, as well as to provide subsidies for public policies aimed at water scarcity. For this, rainfall data were used at stations belonging to the micro-region and its surroundings, for the period from January 1980 to December 2019. In addition, to mitigate the influences caused by temporal heterogeneity, stations with large discontinuity of information. The Inverse Weighted Distance was used to perform the interpolation of data and preparation of maps with isolines of rainfall. The results show the places with the highest annual rainfall during the study period were Serra Talhada and Triunfo, and the lowest rainfall occurred in the vicinity of Ingazeira and Tabira.